The influence of season phase on multivariate load relationships in professional youth soccer - Maughan, P. C.; MacFarlane, N. G.; Swinton, P. A. (Journal of Sports Sciences, 2022)
The purpose of this research was to assess relationships between subjective and external measures of training load in professional youth footballers, whilst accounting for the effect of the stage of the season. Data for ratings of perceived exertion (RPE) and seven global positioning systems (GPS) derived measures were collected from 20 players (age = 17.4 ± 1.3 yrs, height = 178.0 ± 8.1 cm, mass = 71.8 ± 7.2 kg) across a 47-week season. The season was categorised by a pre-season phase, and two competitive phases (Comp1, Comp2). The structure of the data were investigated using principal component analysis. An extraction criterion of component with eigenvalues =1.0 was used. Two components were retained for the pre-season period explaining a cumulative variance of 77.1%. Single components were retained for both Comp1 and Comp2 explaining 73.3% and 74.3% of variance, respectively. Identification of single components may suggest that measures are related and can be used interchangeably, however these interpretations should be considered with caution. The identification of multiple components in the pre-season phase suggests that univariate measures may not be sufficient when considering load experienced. These results suggest that factoring load based on measures of volume and intensity should be considered.